Archives of Bessarabia (5). Year I, no. 4 from October - December 1929 (Confluenţe Bibliologice, 2022)
This article reveals interesting testimonies related to the lives of Moldovans who suﬀered during foreign occupations. Researching the magazine Arhivele Bessarabiei, year I, No. 4 from October - December 1929, T. G. Bulat discovers a letter written by Constantin Ghica, Iordache Balș and countersigned by Iordache Roset, on behalf of the Divan of Moldova, addressed to the Russian knight senator S. S. Cușnicov, in the year 1808. Also presented is a princely charter issued by Mihail Vodă Suțu, by which the old royal decrees are conﬁrmed to the hermitage in the Ceahlău mountain, which is signed and on which the great red royal seal is applied on February 15, 1820.
Keywords: the history of the Romanians; Archives of Bessarabia Magazine